The impact of teaching presence on students’ online learning experience: evidence from 334 Chinese universities during the pandemic - Li, Wen; Wang, Weiping (Frontiers in Psychology, 2024)
Teaching presence is the core role of teachers in online education and is the most promising mechanism for developing online learning communities. Drawing on the theoretical framework of teaching presence, and based on data from an online survey of university students from 334 Chinese universities, this study constructs a framework for teaching presence and compares the differences in teaching presence among different student groups, and further explores the impact of teaching presence on students' online learning experience and its heterogeneity in terms of gender and discipline. The study finds that teaching presence includes three dimensions: instructional design and organization, facilitating interaction, and direct instruction, and there are differences among different groups. Teaching presence has a significant impact on the online learning experience, among which facilitating interaction is the most important influencing factor. Heterogeneity examination reveals that the direct instruction dimension has a greater impact on the online learning experience of female students and students in science and engineering, while the facilitating interaction dimension has a greater impact on the experience of male students and students in science and engineering. For the development of online teaching, it is necessary to help online teachers comprehensively improve teaching presence, adopt different teaching strategies and improvement measures for different student groups, and pay attention to collecting and analyzing student behavioral data for teachers to reflect on and improve teaching.